The crystal structure of 2,5-bis(3,5-dimethylphenyl)thiazolo[5,4-d]thiazole, C20H18N2S2 - Zhai Zhi-Wei; Yang Shuang-Hua (Zeitschrift für Kristallographie - New Crystal Structures)
C20H18N2S2, monoclinic, P21/n (no. 14), a = 7.92140(10) Å, b = 6.08080(10) Å, c = 17.8091(3) Å, β = 90.592(2)°, V = 857.79(2) Å3, Z = 4, Rgt(F) = 0.0382, wRref(F2) = 0.1051, T = 149.99(10) K.